A generalization of semiperfect modules - Türkmen, B. N. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
A module M is called radical semiperfect, if MN has a projective cover whenever Rad(M) N M. We study various properties of these modules. It is proved that every left R-module is radical semiperfect if and only if R is left perfect. Moreover, radical lifting modules are defined as a generalization of lifting modules.